Long-Term and Short-Term Effects of Hemodialysis on Liver Function Evaluated Using the Galactose Single-Point Test. (10th July 2014) - Hou, Yi-Chou; Liu, Wen-Chih; Liao, Min-Tser; Lu, Kuo-Cheng; Lo, Lan; Pan, Heng-Chih; Wu, Chia-Chao; Hu, Oliver Yoa-Pu; Tang, Hung-Shang
Abstract : Aim . The galactose single-point (GSP) test assesses functioning liver mass by measuring the galactose concentration in the blood 1 hour after its administration. The purpose of this study was to investigate the impact of hemodialysis (HD) on short-term and long-term liver function by use of GSP test. Methods . Seventy-four patients on maintenance HD (46 males and 28 females, 60.38 ± 11.86 years) with a mean time on HD of 60.77 ± 48.31 months were studied. The GSP values were compared in two groups: (1) before and after single session HD, and (2) after one year of maintenance HD. Results . Among the 74 HD patient, only the post-HD Cr levels and years on dialysis were significantly correlated with GSP values (r = 0.280, P < 0.05 and r = - 0.240, P < 0.05, resp.). 14 of 74 patients were selected for GSP evaluation before and after a single HD session, and the hepatic clearance of galactose was similar (pre-HD 410 ± 254 g/mL, post-HD 439 ± 298 g/mL, P = 0.49 ). GSP values decreased from 420.20 ± 175.26 g/mL to 383.40 ± 153.97 g/mL after 1 year maintenance HD in other 15 patients (mean difference: 19.00 ± 37.66 g/mL, P < 0.05 ). Conclusions . Patients on maintenance HD for several years may experience improvement of their liver function. However, a single HD session does not affect liver function significantly as assessed by the GSP test. Since the metabolism of galactose is dependent on liver blood flow and hepatic functional mass, further studies are needed.